A large‐scale experimentation of the smart sewage system. (11th June 2017) - Abbas, O.; Abou Rjeily, Y.; Sadek, M.; Shahrour, I.
Abstract: This paper presents a large‐scale experimentation of the smart sewage system, which is conducted at the Campus of Lille University. The campus stands for a town of about 25 000 users with 150 buildings and 100 km urban networks. The experimentation is carried out within a large‐scale demonstrator of the Smart City, which includes a smart monitoring of the drinking water, sewage, electrical and district heating networks. The originality of this paper lies in the integrated approach, which includes smart monitoring as well as data collection and analysis. The monitoring of the drinking water and sewage networks allows the use of numerical modelling of and the detection of eventual connection between the sewage and storm water systems. The paper shows how the smart technology could be implemented and used to enhance our understanding of the sewage system and to improve its management.